The B-Fest Promotion Model by the Local Government During the Covid-19 Pandemic Recovery Period (A Case Study at an Annual Tourism Event in Banyuwangi District) - Hanggraito, Ahmadintya Anggit; Tyas, Inno Cahyaning; Ratri, Arum Andary (KnE Social Sciences, 2024)
At the start of the Covid-19 pandemic, the Asia Pacific region experienced a decline in tourist arrivals by 82% from January-October 2020. This problem caused event promotion space to decrease in various parts of the world. The Covid-19 pandemic in Banyuwangi was first confirmed on March 29, 2020. Banyuwangi was one of the areas that felt the impact of this crisis. This research aims to reveal the B-fest promotion model by the Banyuwangi District government during the recovery period from the Covid-19 pandemic. This research uses a case study method with a qualitative approach. Data collection uses in-depth interviews and market surveys. The market survey used 284 respondents from tourists and non-tourists who had seen promotions from B-Fest 2022. This research shows that local government policies in carrying out promotions for B-fest events support the economic recovery process. The interactional communication model is the promotion concept carried out by the local government. However, this promotion model shows the supporting and inhibiting aspects of the promotion model itself. Keywords: festival, promotion, local government, tourism communication, Banyuwangi, pandemic recovery period